1996
DOI: 10.1007/s004410050548
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the peritrophic matrix of the tsetse fly, Glossina morsitans morsitans

Abstract: The three-layered peritrophic matrix of Glossina morsitans morsitans is shown, by histochemistry, to be formed of a mixture of glycosaminoglycans, glycoproteins and chitin. In all three layers the glycosaminoglycans contain GlcNAc-hexuronic and Gal-GlcNAc moieties, together with chitin. Glycosaminoglycans in layer 3 are sulphated and sulphated sites have a mean interspace distance of 53 nm - similar to the spacing of fixed charge sites in glomerular basement membrane suggesting a rôle for these sites in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…A solid NMR analysis showed that proteins accounted for 60% of the PM in Manduca sexta larvae (Kramer et al, 1995). The number of proteins in PMs vary from species to species (Stamm et al, 1978;Adang and Spence, 1982;Dorners and Peters, 1988;Derksen and Granados, 1988;Lehane et al, 1996;Moskalyk et al, 1996). In Type 1 PMs, for example, the number of proteins can be from 2 to about 30 with molecular weights ranging from 14 to over 200 kD by SDS-PAGE analysis (Adang and Spence, 1982;Rupp and Spence, 1985;Derksen and Granados, 1988;Ramos et al, 1994).…”
Section: Biochemical Composition Of Pmsmentioning
confidence: 96%
See 1 more Smart Citation
“…A solid NMR analysis showed that proteins accounted for 60% of the PM in Manduca sexta larvae (Kramer et al, 1995). The number of proteins in PMs vary from species to species (Stamm et al, 1978;Adang and Spence, 1982;Dorners and Peters, 1988;Derksen and Granados, 1988;Lehane et al, 1996;Moskalyk et al, 1996). In Type 1 PMs, for example, the number of proteins can be from 2 to about 30 with molecular weights ranging from 14 to over 200 kD by SDS-PAGE analysis (Adang and Spence, 1982;Rupp and Spence, 1985;Derksen and Granados, 1988;Ramos et al, 1994).…”
Section: Biochemical Composition Of Pmsmentioning
confidence: 96%
“…In Type 1 PMs, for example, the number of proteins can be from 2 to about 30 with molecular weights ranging from 14 to over 200 kD by SDS-PAGE analysis (Adang and Spence, 1982;Rupp and Spence, 1985;Derksen and Granados, 1988;Ramos et al, 1994). By two-dimensional SDS-PAGE analysis, more proteins could be detected (Lehane et al, 1996;Moskalyk et al, 1996). In both Type 1 and Type 2 PMs, some proteins are glycosylated (Peters, 1992;Lehane, 1997) or even heavily glycosylated (Wang and Granados, 1997a).…”
Section: Biochemical Composition Of Pmsmentioning
confidence: 97%
“…This suggests that strain MIT is devoted to the use of N-acetyl-D-glucosamine and raffinose as primary carbon sources. While polymerized N-acetyl-D-glucosamine (chitin) is known to form the exoskeleton and gut peritrophic membrane of tsetse flies (Lehane et al, 1996;Wigglesworth, 1972), little is known about the presence of raffinose in this insect. In the maize weevil, Sitophilzrs zeamais, an insect known to harbour closely related S-endosymbionts, raffinose is known to be an important dietary component (Baker, 1991).…”
Section: Carbon Substrate Assimilation Testsmentioning
confidence: 99%
“…[17] As revealed by electron microscopy, four different layers of chitin fibrils and glycoproteins (e.g. peritrophins) [54,55] are secreted at the beginning of the anterior midgut by the proventriculus [56] and self-assemble to form the PM. [56] Peritrophin genes are also expressed in more distal parts of the midgut, suggesting that this barrier is remodeled along the length of the gut.…”
Section: Hold It Tight: the Drosophila Gut Anatomymentioning
confidence: 99%